أهمية الرقمنة في تنظيم وتسيير المؤسسات الرياضية دراسة ميدانية مديرية الشباب والرياضة بالمسيلة - لعلاوي، ساسي; Supervisor :د. نويري ،بوبكر (Mohamed Boudiaf University of M'sila, 2024)
الملخص : تمثل الرقمنة تحولًا جذريًا في طريقة تعاملنا مع المعلومات وتسيير العمليات في مختلف المجالات، ولها تأثير كبير على الإدارة الرياضية. تعتبر الرقمنة أداة فعالة لتحسين كفاءة التشغيل وتعزيز التفاعل مع المشجعين وتطوير الأداء الرياضي وتسيير وتنظيم الإدارة الرياضية للمؤسسات والمنشآت الرياضية، حيث تسهم الرقمنة في تحسين عمليات الإدارة الرياضية من خلال استخدام أنظمة إدارة متقدمة وتطبيقات تسهل التواصل وتنظيم الموارد. ومن خلال دراستنا التي جاءت تحت عنوان أهمية الرقمنة في تسيير وتنظيم الإدارة الرياضية بمديرية الشباب والرياضة لولاية المسيلة، حيث استنتجنا أن الرقمنة أداة قوية في تطوير الإدارة الرياضية وتحسين الأداء الرياضي بشكل عام. ومع الفرص الرقمية المتاحة والتحديات المعاصرة، يجب على الأندية والمنظمات الرياضية استثمارها والعمل على تطويرها. عنوان الدراسة : أهمية الرقمنة في تنظيم وتسيير المؤسسات الرياضية دراسة ميدانية مديرية الشباب والرياضة بالمسيلة أهداف الدراسة :. - التعرف على مدى وجود رقمنة بمديرية الشباب والرياضة بولاية المسيلة - معرفة تأثير الرقمنة على التسيير بمديرية الشباب والرياضة بولاية المسيلة - التعرف على دور الرقمنة في تنظيم مديرية الشباب والرياضة بولاية المسيلة - إعطاء نظرة واضحة تكمن في قدرة الرقمنة على التأثير في تسيير وتنظيم الإدارات الرياضية - إبراز العلاقة الوطيدة التي تربط الرقمنة بتنظيم وتسيير الإدارة الرياضية. - معرفة مدى تأثير الرقمنة على تحسن الأداء الوظيفي للإدارة الرياضية بمديرية الشباب والرياضة بالمسيلة - الوصول إلى المعارف والحقائق العلمية حول أهمية الرقمنة في تنظيم وتسيير الإدارة الرياضية التساؤل العام الدراسة : - ما دور الرقمنة في تنظيم وتسيير المؤسسات الرياضية؟ التساؤلات الجزئية : 1. هل هناك أثر ايجابي ذو دلالة احصائية لوجود رقمنة على مستوى إدارات مديرية الشباب والرياضة لولاية المسيلة؟ 2. هل هناك أثر ايجابي ذو دلالة احصائية لوجود دور للرقمنة في تسيير مديرية الشباب والرياضة بولاية المسيلة؟ 3. هل هناك أثر ايجابي ذو دلالة احصائية على وجود دور للرقمنة في تنظيم مديرية الشباب والرياضة بولاية المسيلة؟ الفرضية العامة للدراسة : - يوجد دور للرقمنة في تنظيم وتسيير المؤسسات الرياضية الفرضيات الجزئية 1. يوجد أثر ايجابي ذو دلالة احصائية لوجود رقمنة على مستوى إدارات مديرية الشباب والرياضة لولاية المسيلة 2. لا يوجد أثر ايجابي ذو دلالة احصائية لوجود دور للرقمنة في تسيير مديرية الشباب والرياضة بولاية المسيلة 3. لا يوجد أثر ايجابي ذو دلالة احصائية على وجود دور للرقمنة في تنظيم مديرية الشباب والرياضة بولاية المسيلةا المنهج المتبع في الدراسة : انطلاقا من طبيعة الموضوع المعالج في بحثنا هذا والذي نقوم من خلاله بوصف الظواهر التي تتمحور عموما حول أهمية الرقمنة في تنظيم وتسيير الإدارة الرياضية فقد اعتمدنا على المنهج الوصفي باعتباره الأنسب لطبيعة الموضوع الأدوات المستخدمة في الدراسة الاستبيان : وقد احتوى استبیان دراستنا على ثلاثة محاور كل محور يضم مجموعة من عبارات، المحور الأول (6) عبارات المحور الثاني (6) عبارات، والمحور الثالث (6) عبارات، وركزنا في تكوينها على عاملي البيئة واللغة المستعملة وسلاسة المفردات مع وضوح العبارات وبساطتها قدر الإمكان. الكلمات المفتاحية بالعربية : الرقمنة، الإدارة الرياضية، التسيير والتنظيم، مديرية الشباب والرياضة. digitization، sports management، management and بالإنجليزية organization، Youth and Sports Directorate. جاء هذا البحث في فصول . الفصل الأول: ................. الإطار العام للدراسة............................... وتناول الفصل الثاني: ............ أساسيات حول الإدارة الرياضية......................... أما الفصل الثالث................. أساسيات حول المؤسسات الرياضية....................... الفصل الرابع:........................ منهجية الدراسة........................... ............ الفصل الخامس:........................ عرض وتحليل ومناقشة النتائج...................... من أهم النتائج التي توصل إليها الباحث مما سبق وبناءاً على مخرجات البرنامج الإحصائي spss والنتائج المحصلة منه وبالأدوات الإحصائية المستعملة نستخلص النتائج التالية: - من اختبارنا للفرضية الأولى والتي مفادها: يوجد أثر ايجابي ذو دلالة احصائية لوجود رقمنة على مستوى إدارات مديرية الشباب والرياضة لولاية المسيلة توصلنا إلى صحة هذه الفرضية حيث استنتجنا أن هناك تطبيق للرقمنة في مديرية الشباب والرياضة بولاية المسيلة من خلال ما لمسناه من إجابات المبحوثين ومن خلال توفر عتاد الإعلام الآلي وملحقاته وتحديثها وصيانتها كلما تطلب الأمر، في مديرية الشباب والرياضة بالإضافة لوجود تكوين ودورات تدريبية لموظفين في المديرية على استخدام واستعمال الوسائل الرقمية والالكترونية، وكذلك توفر شبكة الاتصالات والبرامج والتطبيقات التي تسمح للموظفين بتسهيل عملية رقمنة العمل الإداري بالمديرية، اتفقت نتائج الفرضية مع نتائج دراسة بلبصير عيسى، من حيث تواجد واستعمال للرقمنة داخل المؤسسة. - من اختبارنا للفرضية الثانية والتي مفادها: لا يوجد أثر ايجابي ذو دلالة احصائية لوجود دور للرقمنة في تسيير الإدارة الرياضية في مديرية الشباب والرياضة بولاية المسيلة حيث توصلنا إلى عدم صحة هذه الفرضية فمن خلال إجابات أفراد العينة تبين وجود عكس ذلك حيث تلعب الرقمنة دوراً حيوياً في تسيير الإدارة الرياضية من خلال تحسين الكفاءة والفعالية في مختلف جوانب العمليات الرياضية وهذا نظرا لمساهمة الرقمنة في تسريع عملية تبادل المعلومات وحفظها، والرقابة على العمل الإداري وتقريب الإدارة من المواطن والمساهمة في صنع القرار في جميع المستويات التنظيمية وتقليل الأخطاء المرتكبة، تناسبت نتائج هذه الفرضية مع دراسة محمد بودالي، من خلال تحسين جودة الخدمة وتحسين الخدمة العمومية . - من اختبارنا للفرضية الثالثة والتي مفادها لا يوجد أثر ايجابي ذو دلالة احصائية على وجود دور للرقمنة في تنظيم الإدارة الرياضية بمديرية الشباب والرياضة بولاية المسيلة حيث توصلنا إلى عدم صحة هذه الفرضية نظرا لوجود دلالة احصائية على وجود دور للرقمنة في تنظيم الإدارة الرياضية بمديرية الشباب والرياضة بولاية المسيلة وذلك من خلال تحسين الكفاءة، وتبسيط العمليات، وزيادة الشفافية وتحقيق مستوى أعلى من التنظيم والكفاءة، مما يعزز من تطور القطاع الرياضي بشكل عام، من خلال تسهيل المعلومات اللازمة وتنظيمها وتوفير الجهد وتقليل التكاليف و واختصار الوقت، اتفقت نتائج هذه الفرضية مع نتائج دراسة أحمد علي من حيث تحسين الكفاءة الإدارية وتوفير الوقت والجهد، وتقليل من الأخطاء الإدارية. كما ساعدت في تحسين التواصل بين الإدارات المختلفة. أهم التوصيات :. - استخدام تقنيات الذكاء الاصطناعي لتحليل البيانات بشكل أكثر عمقاً وتقديم توقعات واستشارات تستند إلى البيانات. - إنشاء أنظمة متكاملة تجمع بين إدارة البيانات والتواصل وتحليل الأداء يمكن أن يرفع من كفاءة العمل الإداري بشكل كبير. - ضرورة توفير برامج تدريبية مستمرة للموظفين للتأكد من قدرتهم على استخدام الأدوات الرقمية بشكل فعال. - الشراكة مع شركات التقنية يمكن أن يساعد في تطوير حلول مخصصة تلبي احتياجات الإدارة الرياضية بشكل دقيق. Searchlight in English Faculty Institute of Sciences and Sports and Technical and Physical Activities Department: Order No: ......................................................... No. d 'registration : ........... 202323044102102 Searcher : ...........................LALAOUI SACI...................................... Publicly supported on :............................................................................ Title of the thesis (dissertation): The importance of digitization in organizing and managing sports institutions - A field study of the Directorate of Youth and Sports in M'Sila Language of the thesis: .....................ARABIC................................... Model of the thesis: A memorandum submitted as part of the requirements for obtaining a master’s degree Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor BOUBAKRE NOUIRI Grade: Professor Lecturer A Lecturer Number of pages: .92 Option: - Identifying the extent of digitization in the Directorate of Youth and Sports in the state of M’sila - Knowing the impact of digitization on the management of the Youth and Sports Directorate in the state of M’sila - Identifying the role of digitization in organizing the Youth and Sports Directorate in the state of M’sila - Giving a clear view of the ability of digitization to influence the management and organization of sports departments - Highlighting the close relationship between digitization and the organization and management of sports administration. - Knowing the extent of the impact of digitization on improving the functional performance of the sports administration in the Youth and Sports Directorate in M’sila - Access to scientific knowledge and facts about the importance of digitization in organizing and managing sports administration Summary: Digitization represents a radical shift in the way we deal with information and conduct operations in various fields، and it has a major impact on sports management. Digitization is an effective tool for improving operating efficiency، enhancing interaction with fans، developing sports performance، and managing and organizing sports management for sports institutions and facilities، as digitization contributes to improving sports management processes through the use of advanced management systems and applications that facilitate communication and organization of resources. Through our study، which came under the title The Importance of Digitization in the Management and Organization of Sports Administration in the Directorate of Youth and Sports of M’Sila State، we concluded that digitization is a powerful tool in developing sports administration and improving sports performance in general. With the available digital opportunities and contemporary challenges، sports clubs and organizations must invest in them and work to develop them Title of the study: The importance of digitization in organizing and managing sports institutions - A field study of the Directorate of Youth and Sports in M'Sila The purpose of the study: - Trying to know the extent of the impact of digitization on the organization and management of sports administration. - The reality of applying digitization in all sectors, including the sports sector - Knowing the relationship between digitization and sports administration management Problem: - What is the role of digitization in organizing and managing sports institutions? Hypotheses: 1. There is a positive, statistically significant effect of the presence of digitization at the level of departments of the Directorate of Youth and Sports in the state of M’sila. 2. There is no statistically significant positive effect due to the presence of a role for digitization in the management of the Youth and Sports Directorate in the state of M’sila. 3. There is no statistically significant positive impact on the presence of a role for digitization in organizing the Youth and Sports Directorate in M’Sila state. Key words digitization، sports management، management and organization، Youth and Sports Directorate - The most important results achieved are: From the above, and based on the outputs of the SPSS statistical program, the results obtained from it, and the statistical tools used, we conclude the following results: 1. From our testing of the first hypothesis, which states: There is a positive, statistically significant effect of the presence of digitization at the level of departments of the Directorate of Youth and Sports in the state of M’sila, we reached the validity of this hypothesis, as we concluded that there is an application of digitization in the Directorate of Youth and Sports in the state of M’sila, through what we observed from the answers of the respondents and through The availability of automated media equipment and its accessories, updating and maintaining them whenever necessary, in the Directorate of Youth and Sports, in addition to the presence of training and training courses for employees in the Directorate on the use and use of digital and electronic means, as well as the availability of a communications network, programs and applications that allow employees to facilitate the process of digitizing administrative work in the Directorate. The results of the hypothesis agreed with Results of Belbasir Issa’s study, in terms of the presence and use of digitization within the organization. 2. From our test of the second hypothesis, which states: There is no statistically significant positive effect of the existence of a role for digitization in the management of sports administration in the Youth and Sports Directorate in the state of M’sila, where we concluded that this hypothesis is not true. Through the answers of the sample members, it was revealed that there is the opposite, as digitization plays a vital role in Managing sports administration by improving efficiency and effectiveness in various aspects of sports operations. This is due to the contribution of digitization in accelerating the process of exchanging and preserving information, monitoring administrative work, bringing the administration closer to the citizen, contributing to decision-making at all organizational levels, and reducing committed errors. The results of this hypothesis are consistent with the study Muhammad Boudali, by improving the quality of service and improving public service. 3. From our testing of the third hypothesis, which states that there is no positive impact with statistical significance on the presence of a role for digitization in organizing the sports administration in the Directorate of Youth and Sports in the state of M’sila, we concluded that this hypothesis is not correct due to the presence of statistical evidence that there is a role for digitization in organizing the sports administration in the Directorate of Youth and Sports in the state of M’sila. Al-Masila, by improving efficiency, simplifying operations, increasing transparency, and achieving a higher level of organization and efficiency, which enhances the development of the sports sector in general, by facilitating and organizing the necessary information, saving effort, reducing costs, and shortening time. The results of this hypothesis agreed with the results of Ahmed’s study. In terms of improving administrative efficiency, saving time and effort, and reducing administrative errors. It also helped improve communication between different departments.
Keywords: الرقمنة; الإدارة الرياضية; التسيير والتنظيم; مديرية الشباب والرياضة